Translation Analysis on Passive Voice from Indonesian into English Found in "Gua Sunyaragi" Book - Apandi, Apandi; Islami, Fajry Nur (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2018)
This research aimed at analyzing the translation of passive voice from Indonesian into English and finding out how the passive sentences were translated. The qualitative descriptive method was applied in this research. The data were gathered from the book GuaSunyaragi by group 6 of Indonesian-English Translation class (2017). The analyzed data were limited only to the first section of GuaSunyaragi. The researcher followed some steps in analyzing the data, first was classifying the collected data, then the researcher anaylized the data based on grammatical and semantics approach, then the researcher put the result into tables, and the last step was to draw the conclusion. The findings have shown that there are 32 passive sentences found in the GuaSunyaragi book.21 (65.62 %) of the data were passive sentences that were translated into passive sentences, 7 (21.86%) were passive sentences that were translated into active sentences, 2 (6.25%) were passive sentences that were translated into sentence with whiz deletion, and 2 (6.25%) were passive sentences that were translated into active sentences with preposition. Translation shift occasionally occurs in the process of translation in order to create a natural translation from the SL to the TL.